The global landscape of pediatric monoclonal antibody (mAb) clinical trials: an analysis of ClinicalTrials.gov - Agrata Sharma; Sanjana Mukherjee; Sharonann Lynch (Frontiers in Pediatrics, 2026)
Introduction Monoclonal antibodies (mAbs) are a growing class of biologics used to address many diseases, including cancers, autoimmune diseases, and infectious diseases, with several mAbs specifically approved for use in children for various indications. However, developing and using mAbs in pediatric populations is particularly challenging due to limited clinical trial data in children, which stems from recruitment difficulties, ethical considerations, and other issues. Furthermore, inconsistent access to clinical trials, especially in low- and middle-income countries (LMICs), hinders the widespread accessibility and applicability of mAbs. To highlight challenges and opportunities, this study reviews the global pediatric mAb clinical trials data. Methods Using a cross-sectional design, data were extracted from ClinicalTrials.gov, the largest clinical trials database, managed by the U.S. National Library of Medicine (NLM) at the National Institutes of Health (NIH). Clinical trials were analyzed by geographic location, country income classification, and trial characteristics such as sponsor type and reasons for termination. Results Our analysis identified 1,863 mAb clinical trials registered on ClinicalTrials.gov that permitted pediatric enrollment, of which only 239 (12.8%) exclusively enrolled pediatric populations. Most trials were conducted in high-income countries in the Global North, with trials in high-income countries outnumbering those in low-income countries by more than 200-fold, revealing significant inequities in clinical trial participation by geographic region. Of all mAb trials permitting pediatric enrollment, only 168 (9.0%) targeted an infectious disease indication; bacterial, fungal, and neglected tropical diseases were particularly underrepresented. Low patient accrual and trial attrition were the most commonly cited reasons for trial termination. Our results also revealed a significant transparency gap: fewer than one third of trials posted results, and only a small fraction made study protocols, statistical analysis plans, and informed consent forms publicly available, despite mandatory disclosure requirements. Discussion The findings suggest that mAb clinical trials permitting pediatric enrollment are geographically concentrated, disease-selective, and insufficiently transparent. These findings can inform policy and investment decisions to ensure equitable and transparent research on mAbs for pediatric populations.